Image of Vishnu and goddess Chamunda in the Devakoshthas (niches) - Temples of India Project Team (Jio Institute, 2024)
The north-facing lateral transept of the mandapa (pillared hall) of the Mahanaleshwar Temple has three devakoshthas (niches), of which the two on the right are seen here. The devakoshthas at the centres of the dwarf pillars house an icon of Vishnu and, on the left, an image of Chamunda. The goddess is depicted as having a skeletal body, sagging breasts, fangs, and matted hair. Her two attendants are shown similarly. As attributes, she holds a kapala (human skull) and a dagger.